The Efforts Of Bengkulu Regional Police Investigators In Determining Corruption Suspects For Soybean Seed Procurement At Department Of Agriculture Of Bengkulu Province For Fiscal Year 2016 - Dedy SV Simanjuntak; Hamzah Hatrik; Lidia Br Karo (Universitas Bengkulu, 2022)
Bengkulu Regional Police Investigators carried out their efforts by conducting investigations to determine suspects from state financial losses arising from the disbursement of advances for the work of procuring soybean seeds at the Department of Agriculture of Bengkulu Province for Fiscal Year 2016. The investigation was done because the work on procurement of goods and services had not been completed, but state finances had already been loss, although the control and supervision activities were under the authority of PPK (the Commitment Making Officer), in this case, KPA (the Budget User Authority) still involved itself. This research was empirical juridical research with descriptive research type. Sources of data applied were primary and secondary data. Data processing was carried out using the editing method, then data analysis was using qualitative analysis methods, by means of inductive-deductive thinking or vice versa. The purpose of this study was to find out the efforts of Bengkulu Regional Police investigators in determining suspects and the juridical basis of investigators in determining the suspects of corruption in the procurement of soybean seeds at the Department of Agriculture of Bengkulu Province for Fiscal Year 2016. The results of this study indicated that: (1) The Efforts of Bengkulu Regional Police Investigators in determining the suspect of corruption in the procurement of soybean seeds by examining witnesses, which was a team of directors from the Department of Agriculture of Bengkulu Province and the implementing parties, as well as witnesses involved in carrying out the work, conducting inspections and confiscation of documents, and finally asking for information from experts. (2) The investigators' juridical basis in determining 3 (three) suspects; the Budget User Authority (KPA) who also served as the Head of the Department of Agriculture of Bengkulu Province, the Commitment Making Officer (PPK), and the Deputy Executive Director of corruption activities in the procurement of soybean seeds at the Department of Agriculture of Bengkulu Province for the 2016 Fiscal Year, was applying Article 3 of the Law of the Republic of Indonesia Number 31 of 1999 as amended by the Law of the Republic of Indonesia Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption.